2012
DOI: 10.1371/journal.pone.0046916
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Immune Responses to the 7-Valent Pneumococcal Conjugate Vaccine in the First 2 Years of Life

Abstract: BackgroundThe CRM197-conjugated 7-valent pneumococcal vaccine (PCV7) is protective against vaccine serotype disease and nasopharyngeal carriage. Data on PCV7-induced mucosal antibodies in relation to systemic or natural anticapsular antibodies are scarce.MethodsIn a randomized controlled setting, children received PCV7 at age 2 and 4 months (2-dose group), at age 2, 4 and 11 months (2+1-dose group) or no PCV7 (control group). From 188 children paired saliva samples were collected at 12 and 24 months of age. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In line with a study conducted in the Netherlands, we found that serum and saliva IgG antibodies were correlated after booster vaccination [21] . Whereas it is likely that the IgG antibodies present at moderate levels in saliva after primary PCV immunization and at higher levels after PPV booster vaccination diffused from serum, some IgG may have been produced in the upper respiratory mucosa.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with a study conducted in the Netherlands, we found that serum and saliva IgG antibodies were correlated after booster vaccination [21] . Whereas it is likely that the IgG antibodies present at moderate levels in saliva after primary PCV immunization and at higher levels after PPV booster vaccination diffused from serum, some IgG may have been produced in the upper respiratory mucosa.…”
Section: Discussionsupporting
confidence: 91%
“…Possibly this early colonization stimulates the development of mucosal vaccine responses, unlike systemic vaccine responses that reportedly may be suppressed in individuals colonized with vaccine serotypes before vaccination [34] , [35] . Findings are more consistent for responses after booster vaccination with studies from the UK, Finland and the Netherlands reporting that PCV-serotype-specific salivary IgA and IgG responses are increased in PCV-primed children after booster vaccination with PPV or PCV [19] , [21] , [33] . In line with these studies in low-risk children, we have demonstrated that PCV primes for immune memory responses that result in enhanced mucosal IgA and IgG antibody responses to subsequent booster vaccination even when PCV is given at very young age.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is probably due to the mechanism of mucosal transportation; which is known to be passive for IgG (high blood concentration is required) and active for IgA. In addition, covalently conjugated polysaccharide vaccines, applied parenterally, contribute to the control of the infection by indirect protection by reducing the carriage rates ( 35 ) and herd immunity ( 36 , 37 ), but salivary anticapsular IgA-levels seem to respond much better to natural boosting ( 38 ). Nevertheless, the influence of carriage over immunization is not clear.…”
Section: Key Features In Modern Vaccinology Linked With the Developmementioning
confidence: 99%
“…Polysaccharides need a coupling molecule and, thus, an additional step for conjugating them onto the microspheres. Several methods for conjugation to microspheres have been developed using polysaccharides from different bacterial species (6,8,9,(11)(12)(13)(14)(15). A comparative study of different coupling agents showed that the nontoxic 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium (DMTMM) was the overall preferred coupling agent when conjugating pneumococcal polysaccharides to microspheres (15).…”
mentioning
confidence: 99%